HE4 Levels in Ovarian Cancer-Resistant Menopausal Women: Kadar HE4 pada wanita menopause yang resisten kanker ovarium - Wiwi Irawan; Syahrul Rauf; Nasrudin A. Mappaware; St. Maisuri T. Chalid (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: To analyse the predictive value of HE4 in ovarian cancer patients according to their resistance and menopausal status Methods: Thirteen premenopausal and twenty-five menopausal ovarian cancer patients were measured for HE4 levels measured using automated chemiluminescent microparticle immunoassay ARCHITECT HE4. Patients categorized into resistant and non-resistant after six cycles of chemotherapy in addition to their clinical symptoms and ultrasound image of cancer. Results: The mean HE4 levels were higher in the resistant group compared with a non-resistant group (274.97 pmol/l vs 128.83 pmol/l; p=0.015). Five menopausal resistant women with HE4 levels >140 pmol/l compared with two women in the non-resistant group. In the pre-menopause group, eight resistant women with HE level >70 pmol/l whereas four women in the non-resistant group. HE levels in menopausal and premenopausal for both ovarian cancers resistant and non-resistant were not significantly different (p>0.05). Conclusion: HE4 levels in resistant ovarian cancer patients are higher compared with non-resistant but do not predict ovarian cancer resistance based on patient menopausal status. Keywords: HE4, ovarian cancer, resistance. Abstak Tujuan: Untuk menganalisis nilai prediktif HE4 pada pasien kanker ovarium berdasarkan resistensi dan status menopausenya Metode: Dilakukan pengukuran kadar HE4 menggunakan metode microparticle immunoassay ARCHITECT HE4 terhadap pasien kanker ovarium terdiri dari 13 perempuan premenopausal dan 25 perempuan menopause. Pasien dikategorikan menjadi resisten dan tidak resisten setelah 6 siklus kemoterapi selain gejala klinis dan gambar USG. Hasil: Rerata kadar HE4 rata-rata lebih tinggi pada kelompok yang resisten dibandingkan dengan kelompok yang tidak resisten (274,97 pmol/l vs 128,83 pmol/l; p=0,015). Terdapat 5 perempuan menopause yang resisten kanker ovarium dan 2 perempuan dalam kelompok yang tidak resisten dengan kadar HE4 >140 pmol/l. Pada kelompok premenopause, 8 perempuan yang resisten dengan tingkat HE >70 pmol/l sedangkan 4 perempuan dalam kelompok tidak resisten. Kadar HE dalam menopause dan premenopause untuk kedua kanker ovarium resisten dan tidak resisten tidak berbeda secara signifikan (p>0,05). Kesimpulan: Kadar HE4 pada pasien kanker ovarium lebih tinggi daripada tidak resisten tetapi tidak memprediksi resistensi kanker ovarium berdasarkan status menopause pasien. Kata kunci : HE4, kanker ovarium, resistensi .